Some Rice Varieties Tolerant to Nitrogen Deprivation - Muhammad Hatta; . Rosmayati; Chairani Hanum; . Hamidah (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2015)
A research on rice varieties tolerant to nitrogen deficiency has been conducted. The experiment was arranged in a split plot design with 3 replicates. There were 15 varieties of rice studied and 2 levels of nitrogen applied, i.e. 0 kg Nha-1 and 90 kg Nha-1. The results showed that rice varieties resistant to nitrogen deficiency were Inpari 16, Marga Sari, Lambur, Inpari 19, Limboto, and Batang Hari. However, rice varieties with high-tolerant to nitrogen deficiency were Marga Sari, Inpari 16, Lambur, Batang Hari, and Situ Patenggang